2015
DOI: 10.1111/bph.13343
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet‐induced metabolic disorders impairs 5‐HT function and anxiety‐like behavior in mice

Abstract: BACKGROUND AND PURPOSEThe link between type 2 diabetes mellitus (T2DM) and depression is bidirectional. However, the possibility that metabolic disorders may elicit anxiogenic-like/depressive-like symptoms or alter the efficacy of antidepressant drugs remains poorly documented. This study explored the influence of T2DM on emotionality and proposed a therapeutic strategy that might be used in depressed diabetic patients. EXPERIMENTAL APPROACHMice were fed a high-fat diet (HFD) and subjected to a full comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 78 publications
9
106
1
3
Order By: Relevance
“…Consistent with this hypothesis, decreased levels of tryptophan were detected in the CNS of patients with T2D (Kloiber et al, 2010;Herrera-Marquez et al, 2011) or in rodents fed an HFD (Kim et al, 2013;Derkach et al, 2015). Using intracerebral microdialysis, we showed that mice fed an HFD displayed lower basal hippocampal extracellular 5-HT concentrations (Zemdegs et al, 2016). Exaggerated stimulation of the monoamine oxidase activity-the enzyme responsible for 5-HT degradation-or the indoleamine 2,3-dioxygenase-the enzyme that metabolizes tryptophan along the kynurenine pathway-are putative explanations for such neurochemical changes Dinel et al, 2014;Gupta et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with this hypothesis, decreased levels of tryptophan were detected in the CNS of patients with T2D (Kloiber et al, 2010;Herrera-Marquez et al, 2011) or in rodents fed an HFD (Kim et al, 2013;Derkach et al, 2015). Using intracerebral microdialysis, we showed that mice fed an HFD displayed lower basal hippocampal extracellular 5-HT concentrations (Zemdegs et al, 2016). Exaggerated stimulation of the monoamine oxidase activity-the enzyme responsible for 5-HT degradation-or the indoleamine 2,3-dioxygenase-the enzyme that metabolizes tryptophan along the kynurenine pathway-are putative explanations for such neurochemical changes Dinel et al, 2014;Gupta et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
“…Evidence also suggests the existence of a positive correlation between IR and major depression (Rasgon and Kenna, 2005). Indeed, the induction of IR in rats or mice, using prolonged exposure to high-fat diet (HFD), causes some hallmark symptoms of depression including anxiety, anhedonia, and despair (Miyata et al, 2004;Ho et al, 2012;André et al, 2014;Gupta et al, 2014;Dutheil et al, 2016;Yang et al, 2016;Zemdegs et al, 2016;Hassan et al, 2018) and exacerbates behavioral abnormalities observed in animal models of depression (Abildgaard et al, 2011;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the mechanisms underlying HFD-induced serotonergic dyshomeostasis and how it translates to an altered mood response is limited. Recently, the anxiogenic/depressive-like phenotype of mice fed a HFD was attributed to an increased sensitivity of the dorsal raphe 5-HT 1A autoreceptor and subsequent reduction in hippocampal 5-HT level [103]. Additionally, the involvement of HFD-induced neuroinflammatory changes in brain regions associated with mood regulation, such as hippocampus has been reported [104].…”
Section: Discussionmentioning
confidence: 99%
“…Because we measured multiple behavioral parameters on each individual duckling, we condensed these non‐independent measures from all trials into two values for each individual using a z ‐score analysis, as described in Guilloux, Seney, Edgar, and Sibille () and Labots, Laarakker, Schetters, Arndt, and van Lith (). This statistical technique has been used in studies to measure emotionality in mice from multiple trials (e.g., Mendez‐David et al., ; Piantadosi et al., ; Shepard et al., ; Zemdegs et al., ). It is an improved way to quantify behavior when using multiple trials because it reduces variance and increases reliability of behavioral measures, compared to using the raw behavioral data (Guilloux et al., ).…”
Section: Methodsmentioning
confidence: 99%